The role of diagnostic laparoscopy in abdominal masses - El Zanati, Hisham I.; Aboelwafaa, Waleed A.; Hamza, Yasser M. (International Surgery Journal, 2020)
Background: Diagnostic laparoscopy is an added tool that has become widely available for the assessment of abdominal masses in addition to conventional imaging. It is the best real time imaging technique due to the magnification and intense illumination provided. The aim of this work is the assessment of the impact of performing diagnostic laparoscopy at the start of operations intended for resection of an abdominal mass. Methods: This prospective study included 40 patients admitted for surgical resection of an abdominal mass. All Patients were subjected to thorough conventional investigations followed by diagnostic laparoscopy performed prior to the start of the definitive operation. We assessed the extra time needed, complications encountered, effect on decision making and the overall benefit of laparoscopy in this context. Results: Overall 21 patients (52.5%) did benefit from diagnostic laparoscopy somehow between upgrading the staging, affecting the laparotomy incision site and confirming feasibility of laparoscopic resection. Of the patients who proceeded to a laparotomy (n=30), diagnostic laparoscopy missed local invasion in 7 patients, which precluded the resection of the tumor in 5 of them. Only 1 complication related to diagnostic laparoscopy was encountered in the form of a port-site hematoma (2.5%). Conclusions: While diagnostic laparoscopy doesn't carry significant added morbidity, it might save the patient an unnecessary laparotomy by altering the preoperative staging and improving the accuracy of anatomical and pathological diagnoses. Laparoscopy has its limitations mainly in the assessment of the retroperitoneal space as well as direct tumor invasion to adjacent organs and vessels.